2021
DOI: 10.1177/1359105321999711
|View full text |Cite
|
Sign up to set email alerts
|

Life on pause: An analysis of UK fertility patients’ coping mechanisms after the cancellation of fertility treatment due to COVID-19

Abstract: In March 2020, fertility clinics across the UK began cancelling all assisted reproductive technology (ART) treatment, with the Human Fertilisation and Embryology Authority (HFEA) stopping all ART treatment from going ahead beyond the 15th April 2020 due to the COVID-19 pandemic. This article examines the coping mechanisms adopted by fertility patients during this time, focussing on the emotional support received from online fertility forums and fertility clinics during the indeterminate wait for treatment to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…There were also specific worries that time may be running out for those awaiting fertility treatment. While this only applied to a couple of the 12 women in the present study, a recent UK survey also identified that cancellation of fertility treatment during the COVID-19 pandemic has caused significant psychological stress, feelings of isolation and weakened coping mechanisms in female fertility patients [45]. Some participants also mentioned that their healthcare professionals (e.g., primary care physicians) were an important source of support and that they were currently unable to easily contact them or have face-to-face appointments.…”
Section: Discussionmentioning
confidence: 74%
“…There were also specific worries that time may be running out for those awaiting fertility treatment. While this only applied to a couple of the 12 women in the present study, a recent UK survey also identified that cancellation of fertility treatment during the COVID-19 pandemic has caused significant psychological stress, feelings of isolation and weakened coping mechanisms in female fertility patients [45]. Some participants also mentioned that their healthcare professionals (e.g., primary care physicians) were an important source of support and that they were currently unable to easily contact them or have face-to-face appointments.…”
Section: Discussionmentioning
confidence: 74%
“…While there have been studies concerning the emotional impact of the suspension of treatments [7][8][9][11][12][13], this is the first to have been conducted in Germany where, in 2020, incidence and case fatality rates were relatively low compared to many other European countries [14]. To our knowledge, it is the first study to assess the possible worries that fertility treatment patients might have concerning an infection with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies in Israel [7], Italy [8], Northeast America and Canada [9,11] and UK [12,13] have also reported that the suspension of fertility treatment has caused substantial distress. Unexpectedly, no demographic factors such as age or education status were significantly associated with the level of distress felt.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological burden on the patients has become a significant issue. One study conducted in England showed that the postponement of ART treatment adversely affected patients’ stress levels [ 3 ]. Enhancing communication between patients and staff had the opposite effect.…”
Section: Discussionmentioning
confidence: 99%